Cemented and uncemented stems for displaced femoral neck fracture in the elderly. Retrospective study with a minimum 1-year follow-up - Regis, Dario; Segalla, Sara; Sandri, Andrea; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Displaced femoral neck fracture (FNF) is a common and significant health issue especially in older population because of the high rates of mortality and complications. The standard surgical treatment is total or partial hip replacement, including a cemented or uncemented stem. The cemented prosthesis is considered the safer option because of a lower rate of periprosthetic fractures (PPFs) as well as an actually reduced risk of bone cement implantation syndrome (BCIS). This retrospective study aims to assess the efficacy and safety of cemented versus uncemented femoral stem for FNF in patients ≥70 years.Methods: 139 patients affected by displaced FNF underwent hip replacement, receiving 89 cemented (64%) and 50 uncemented (36%) stems. Inclusion criteria were: ≥70 years of age, an ICD-9-CM diagnose code 820.00, 820.01, 820.02, 820.03, 820.10, 820.8, and a minimum 1-year follow-up. A p value